THE EFFECT OF IRE (INITIATION-RESPONSE-EVALUATION) STRATEGY IN TEACHING READING COMPREHENSION OF NARRATIVE TEXT AT THE FIRST GRADE OF SMAN OLAHRAGA RIAU PEKANBARU - Megi Andela; Dahler Dahler (Universitas Lancang Kuning, 2017)
The students at first grade of SMAN Olahraga Riau Pekanbaru had some problems in reading narrative text. Based on observation, the researcher tried to solve the phenomena by using IRE (Initation-Response-Evaluation). The purpose of this study was to find the effect between students taught with IRE (Initation-Response-Evaluation) by not using a strategy. Measuring the tested the effectiveness of the IRE (Initation-Response-Evaluation) Strategy in teaching narrative text reading. This type of this research is Quasi Experiments. The population of this study is the first grade of SMA Olahraga Riau Pekanbaru. The population is 99 students. The samples there are 48 students: Xis1 25 students as control class and Xis4 23 students as experiment class. The experimental class result in the average pre-test is (60.00) while the control is 61.40. It was explain that the experiment class value is lower. After the researcher did the treatment with IRE strategy, showing that the average experiment class is higher than the control class with an average of experiment class was 69.78 while in the control class 66.40 from the test results. Researcher got sig value (0.000) < (0.05). In conclusion, there is an effect between students taught by using the IRE strategy by not using a strategy. This strategy is effective in teaching narrative text reading